A Macrophomina phaseolina (Tassi) Goid. kórokozó gomba elleni fungicides védekezés tesztelése in vitro körülmények között - Csüllög, Kitti; Tarcali, Gábor (GEORGIKON FOR AGRICULTURE, 2020)
700 host plants in the world (Békési et. al., 2014). In Hungary, the pathogen causes damage mainly in sunflower, however, in warmer regions it can causes bigger destruction to crop production. There is no effective treatment against the fungus. The special fungal form, the microsclerotium is capable of persisting in the soil for 10 years. Because of that, and because of the many host plants, the crop rotation is not enough solution against the pathogen. If millet or crabgrass is cultivated in the crop rotation the number of microsclerotia in the soil decreases (Ndiaye et. al., 2008). In vivo chemical treatments are ineffective, because of the pathogen is inside the plant under protected conditions. Main target of this research to find a fungicide among those licenced in sunflower that first in vitro and after further experiments in vivo affects fungal growth.
Keywords: Macrophomina phaseolina; sunflower; fungicide; in vitro; microsclerotium